European electricity grid infrastructure expansion in a 2050 context - Jonas Egerer; Clemens Gerbaulet; Casimir Lorenz (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
The European climate targets until 2050 require an adaptation of the generation portfolio in terms of renewable and fossil based generation. Assumptions on the timeline of the targets and the availability and costs of generation technologies are used in energy system models to optimize the cost minimal system transformation. The results include investments in generation technologies and their national allocation. Yet, the models are limited to the national aggregation and lack the spatial resolution required to represent individual network investments and related costs. In this paper, we analyze the impact the results of an energy system model have on demand for network expansion in the European power grid in a line-sharp representation. A cost minimizing mixed-integer problem (MIP) model calculates where in the European electricity grid expansion needs to take place for different time steps (2020/30/40/50) in order to obtain minimal total costs for power plant dispatch and grid expansion. Scenarios based on the generation infrastructure options from the PRIMES EU-wide energy model scenarios invoke different expansion needs and are compared. The model allows investments in the AC network and an overlay DC grid. Resulting investment costs are compared to the numbers of the European Energy Roadmap 2050.
Keywords: C61; H54; L94; 330; Electricity; European Transmission Network; Investment Model